Up in smoke : from legislation to litigation in tobacco politics - Derthick, Martha (CQ Press, 2012)
Tobacco politics has been an issue fraught with significant legal, commercial, and public policy implications. Originally Derthick took a nuanced look at tobacco politics in a new era of 'adversarial legalism' and the consequences, both intended and unintended, of the Master Settlement Agreement. In the 3rd edition, she returns to 'ordinary politics' and the passage of the Family Smoking Prevention and Tobacco Control Act, and shows political institutions working as they should, even if slowly, with partisanship and interest group activity playing their part in putting restraints on cigarette smoking.